2023
DOI: 10.3389/fvets.2023.1043966
|View full text |Cite
|
Sign up to set email alerts
|

Government veterinarians' perceptions of routine biosecurity focused on dairy cattle farms in north-western and north-eastern Spain

Abstract: The implementation of biosecurity measures in livestock production systems can be affected by the psychosocial factors of its stakeholders, which can be observed through their knowledge, attitudes and perceptions/practices. In Spain, there are no regulations per se to promote biosecurity. Of all stakeholders, farmers and veterinarians have been addressed in previous biosecurity studies, but not veterinarians belonging specifically to the government services. This study explores this particular group's percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Further, the present study revealed that awareness about quarantine protocols and their implementation was low in the region. Recent studies have emphasized the importance of advocating the implementation of quarantine protocols as part of dairy farm biosecurity measures in order to prevent the introduction and spread of infectious diseases [32][33][34]. There has been low compliance with testing the maternal immunity of purchased calves, as it is commonly believed that these calves already possess sufficient maternal antibodies against endemic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the present study revealed that awareness about quarantine protocols and their implementation was low in the region. Recent studies have emphasized the importance of advocating the implementation of quarantine protocols as part of dairy farm biosecurity measures in order to prevent the introduction and spread of infectious diseases [32][33][34]. There has been low compliance with testing the maternal immunity of purchased calves, as it is commonly believed that these calves already possess sufficient maternal antibodies against endemic infections.…”
Section: Discussionmentioning
confidence: 99%